Strong magnetoelectric coupling in mixed ferrimagnetic-multiferroic phases of a double perovskite - Kim, M. K. (Sci Rep, 2019)
Exploring new magnetic materials is essential for finding advantageous functional properties such as magnetoresistance, magnetocaloric effect, spintronic functionality, and multiferroicity. Versatile classes of double perovskite compounds have been recently investigated because of intriguing physical properties arising from the proper combination of several magnetic ions. In this study, it is observed that the dominant ferrimagnetic phase is coexisted with a minor multiferroic phase in single-crystalline double-perovskite Er(2)CoMnO(6). The majority portion of the ferrimagnetic order is activated by the long-range order of Er(3+) moments below T(Er) = 10 K in addition to the ferromagnetic order of Co(2+) and Mn(4+) moments arising at T(C) = 67 K, characterized by compensated magnetization at T(Comp) = 3.15 K. The inverted magnetic hysteresis loop observed below T(Comp) can be described by an extended Stoner–Wohlfarth model. The additional multiferroic phase is identified by the ferroelectric polarization of ~0.9 μC/m(2) at 2 K. The coexisting ferrimagnetic and multiferroic phases appear to be strongly correlated in that metamagnetic and ferroelectric transitions occur simultaneously. The results based on intricate magnetic correlations and phases in Er(2)CoMnO(6) enrich fundamental and applied research on magnetic materials through the scope of distinct magnetic characteristics in double perovskites.